Improving the biogas production performance of municipal waste activated sludge via disperser induced microwave disintegration. (October 2016) - Kavitha, S.; Rajesh Banu, J.; Vinoth Kumar, J.; Rajkumar, M.
Graphical abstract: Highlights: Disperser induced microwave pretreatment is a novel sludge disintegration process. This efficient process solubilize organics at 18, 000 kJ/kg TS of specific energy. This pretreatment enhances the disintegration rate efficiently upto 18, 000 kJ/kg TS. The novel process improves VFA production (770 mg/L) efficiently at fermentation. A positive net profit of 104.8 USD/ton of sludge was obtained by this process. Abstract: In this study, the influence of disperser induced microwave pretreatment was investigated to analyze the proficiency of floc disruption on subsequent disintegration and biodegradability process. Initially, the flocs in the sludge was disrupted through disperser at a specific energy input of 25.3 kJ/kg TS. The upshot of the microwave disintegration presents that the solids reduction and solubilization of floc disrupted (disperser induced microwave pretreated) sludge was found to be 17.33% and 22% relatively greater than that achieved in microwave pretreated (9.3% and 16%) sludge alone. The biodegradability analysis, affords an evaluation of parameter confidence and correlation determination. The eventual biodegradability of microwave pretreated, and floc disrupted sludges were computed to be 0.15 (g COD/g COD) and 0.28 (g COD/g COD), respectively. An economic assessment of this study offers a positive net profit of about 104.8 USD/ton of sludge in floc disrupted sample.